OVERCOMING INTERLINGUAL INTERFERENCE AT LANGUAGE LEVELS - Rakhimova Sitora Mashrabjon kizi (Scholar Express Journal, 2021)
The problem of linguistic interference - a process that inhibits the assimilation of a foreign language and arises as a result of the transfer of speech skills from one contacting language to another (from a native language to a foreign one, from a first foreign language to a second) - has been of concern to researchers for more than a decade. This phenomenon has a direct impact on the success of an individual's mastering a foreign language and its use both in receptive and productive types of speech activity.
Keywords: factor, root, reputation, case, determinant